Design of a Digital Illustration-Based Storybook Using the R&D Method in Civics Education for Grade V Students - Pandi Mukarram (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
This study aims to develop a learning media in the form of a digital illustration-based storybook that contains the values of diversity for use in Civics Education (PPKn) for fifth-grade students at SDN 4 Bajur. The development is motivated by the lack of engaging and relevant learning media, impacting low student interest and participation. This research uses the R&D method with the ADDIE development model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation results from three experts indicate the developed digital storybook is in the "highly feasible" category. Material experts gave an average score of 100%, language experts 87.5%, and design experts 91.6%. A trial with 26 fifth-grade students showed that 91.5% of students stated the media is highly feasible, and the post-usage test scored 89.5%. Thus, this digital storybook is suitable as an alternative learning media to enhance students' understanding and interest in learning diversity values in Civics Education.